Influence of heating to high temperatures on mechanical properties of boride-based refractory materials - Lokatkina, Anastasiia; Prikhna, Tetiana; Moshchil, Viktor; Barvitskyi, Pavlo; Borimsky, Oleksandr; Devin, Leonid; Ponomaryov, Semyon; Haber, Richard; Talako, Tatiana; Bondar, Anatoly (Technology audit and production reserves, 2021)
The object of research is HfB2, ZrB2 and ceramics composition HfB2-30 % SiC and ZrB2-20 % SiC, ZrB2-20 % SiC-4 % Si3N4 obtained under high pressure, their mechanical characteristics before and after heating to high temperatures and temperatures of beginning of melting. The research was conducted in order to create new effective refractory materials for use in the aerospace industry. Therefore, the melting temperatures of sintered materials and the effect of heating on their mechanical properties were also studied. Additives (ZrB2-20 % SiC and HfB2-30 % SiC) although led to a decrease in specific gravity. But increased hardness (by 17 % and 46 % in the case of ZrB2 and HfB2, respectively) and fracture toughness (by 40 % and 21 % in the case of ZrB2 and HfB2, respectively). However, significantly reduced the onset of melting temperature in vacuum to 2150–2160 °C. Materials sintered from ZrB2 and HfB2 was not melted after heating to 2970 °C. After heating to a melting point of 2150–2160 °C (in the case of materials with additives) and to temperatures of 2970 °C (in the case of materials sintered with ZrB2 or HfB2), the hardness and fracture toughness decreased. Thus, the hardness of the material prepared from ZrB2 decreased by 19 % and its fracture toughness – by 18 %, and of that prepared from ZrB2–20 % SiC – by 46 % and 32 %, respectively. The hardness of the material prepared from HfB2 decreased by 46 %, its fracture toughness – by 55 %, and of that prepared from HfB2-30 % SiC, after heating decreased by 40 %, but its fracture toughness increased by 15 %. The sintered HfB2 (with a density of 10.4 g/cm3) before heating showed a hardness of HV(9.8 N)=21.27±0.84 GPa, HV(49 N)=19.29±1.34 and HV(98 N)=19.17±0.5, and fracture toughness K1C(9.8 N)=0.47 MH·m0.5, and ZrB2 with a density of 6.2 g/cm3 was characterized by HV(9.8 N)=17.66±0.60 GPa, HV(49 N)=15.25±1.22 GPa and HV(98 N)=15.32±0.36 GPa, K1C(9.8 N)=4.3 MH·m0.5. Material sintered with HfB2-30 % SiC (density 6.21 g/cm3) had Hv(9.8 N)=38.1±1.4 GPa, HV(49 N)=27.7±2.8 GPa, and K1C(9.8 N)=8.1 MH·m0.5, K1C(49 H)=6.8 MH·m0.5. The sintered with ZrB2-20 % SiC material had density of 5.04 g/cm3, HV(9.8 N)=24.2±1.9 GPa, HV(49 N)=16.7±2.8 GPa, K1C(49 H)=7.1 MH·m0.5. The SiC addition to the initial mixture significantly reduces the elasticity of the materials.